2018
DOI: 10.1038/s41598-018-22825-5
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term effects of mild traumatic brain injuries to oculomotor tracking performances and reaction times to simple environmental stimuli

Abstract: Understanding the long-term effects of concussive events remains a challenge for the development of modern medical practices and the prevention of recurrent traumas. In this study, we utilized indices of oculomotor performance and the ability to react to simple environmental stimuli to assess the long-term motor effects of traumatic brain injury in its mildest form (mTBI). We performed analysis of eye movement accuracy, investigated the presence of abnormal eye movements, and quantified time to react to simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Vestibular testing in conjunction with eye-tracking represents a noninvasive method of assessing the peripheral and central deficits in the vestibular and ocular motor systems in many neurological conditions, including brain injury. Work from our group and findings from other studies have shown the utility of ocular motor and vestibular testing in the detection, diagnosis, and monitoring of mTBI, 24,27,28,44,47,48 vestibular, neurotological, and neurological conditions. 12,[21][22][23]35 Appropriate tools for diagnosis and monitoring of the mTBI/concussion have gained significant interest in recent years.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Vestibular testing in conjunction with eye-tracking represents a noninvasive method of assessing the peripheral and central deficits in the vestibular and ocular motor systems in many neurological conditions, including brain injury. Work from our group and findings from other studies have shown the utility of ocular motor and vestibular testing in the detection, diagnosis, and monitoring of mTBI, 24,27,28,44,47,48 vestibular, neurotological, and neurological conditions. 12,[21][22][23]35 Appropriate tools for diagnosis and monitoring of the mTBI/concussion have gained significant interest in recent years.…”
Section: Discussionmentioning
confidence: 82%
“…These tests are commonly used to evaluate ocular motor and vestibular deficits following mTBI and/or other neurological conditions. 24 , 27 , 41 , 42 , 43 , 44 , 45 Metrics describing different components of eye movement (e.g., gain, phase) for each test were computed (detailed description of each metric is included in Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al, 2018). Other relevant findings of our previous research on individuals who had experienced mTBI include poorer accuracy and velocity of rapid eye movements (Danna-Dos-Santos, Mohapatra, Santos, & Degani, 2018), poorer episodic memory (H. Lee et al, 2018), diminished attention and concentration (Carbonar et al, unpublished), and more severe anxiety and sleep disturbance (H.…”
Section: Mtbi and Postural Controlmentioning
confidence: 82%
“…The authors' interpretation of these findings is that they reflect what could happen with poorly administered and inaccurate testing methods. On the other hand, a number of reports have demonstrated utility for reaction time as a concussion assessment (Warden et al, 2001;Willison and Tombaugh, 2006;Cole et al, 2018;Danna-Dos-Santos et al, 2018;Lange et al, 2018). Norris et al (2013) described the reaction time metric as having prognostic utility and others have proposed that reaction time could be used in the absence of baseline measures by just comparing to normative values (Schmidt et al, 2012), and the authors share that opinion based on our recent work.…”
Section: Discussionmentioning
confidence: 99%